Operando Study of LiV3O8 Cathode: Coupling EDXRD Measurements to Simulations. Issue 2 (1st February 2018) - Brady, Nicholas W.; Zhang, Qing; Bruck, Andrea; Bock, David C.; Gould, Christian Alexander; Marschilok, Amy C.; Takeuchi, Kenneth; Takeuchi, Esther; West, Alan C.
Abstract : The electrochemical and phase-change behavior of lithium trivanadate during lithiation and delithiation is analyzed by comparing a coupled electrode/crystal-scale mathematical model to operando experiments. The model expands on a previously published crystal-scale model by adding descriptions for electrode-scale resistances. Agreement between simulated and observed electrochemical measurements is compelling. Time and space-resolved operando EDXRD measurements on the cathode are compared with simulated concentration profiles. Both simulation and experiment reveal that during lithiation, phase transformations preferentially occur near the separator, while during delithiation the disappearance of the lithium-rich β -phase occurs uniformly across the electrode.